MRI and PSMA PET/CT of Biochemical Recurrence of Prostate Cancer - Awiwi, Muhammad O; Gjoni, Migena; Vikram, Raghunandan; Altinmakas, Emre; Dogan, Hakan; Bathala, Tharakeswara K; Naik, Sagar; Ravizzini, Gregory; Kandemirli, Sedat Giray; Elsayes, Khaled M; Salem, Usama I (Radiographics, 2023)
Prostate cancer may recur several years after definitive treatment, such as prostatectomy or radiation therapy. A rise in serum prostate-specific antigen (PSA) level is the first sign of disease recurrence, and this is termed . Patients with biochemical recurrence have worse survival outcomes. Radiologic localization of recurrent disease helps in directing patient management, which may vary from active surveillance to salvage radiation therapy, androgen-deprivation therapy, or other forms of systemic and local therapy. The likelihood of detecting the site of recurrence increases with higher serum PSA level. MRI provides optimal diagnostic performance for evaluation of the prostatectomy bed. Prostate-specific membrane antigen (PSMA) PET radiotracers currently approved by the U.S. Food and Drug Administration demonstrate physiologic urinary excretion, which can obscure recurrence at the vesicourethral junction. However, MRI and PSMA PET/CT have comparable diagnostic performance for evaluation of local recurrence after external-beam radiation therapy or brachytherapy. PSMA PET/CT outperforms MRI in identifying recurrence involving the lymph nodes and bones. Caveats for use of both PSMA PET/CT and MRI do exist and may cause false-positive or false-negative results. Hence, these techniques have complementary roles and should be interpreted in conjunction with each other, taking the patient history and results of any additional prior imaging studies into account. Novel PSMA agents at various stages of investigation are being developed, and preliminary data show promising results; these agents may revolutionize the landscape of prostate cancer recurrence imaging in the future. RSNA, 2023 Quiz questions for this article are available through the Online Learning Center. See the invited commentary by Turkbey in this issue. The slide presentation from the RSNA Annual Meeting is available for this article.